2017
DOI: 10.18632/oncotarget.18151
|View full text |Cite
|
Sign up to set email alerts
|

Rumen-derived lipopolysaccharide provoked inflammatory injury in the liver of dairy cows fed a high-concentrate diet

Abstract: Rumen-derived lipopolysaccharide (LPS) is translocated from the rumen into the bloodstream when subacute ruminal acidosis (SARA) occurs following long-term feeding with a high-concentrate (HC) diet in dairy cows. The objective of this study was to investigate the mechanism of inflammatory responses in the liver caused by HC diet feeding. We found that SARA was induced in dairy cows when rumen pH below 5.6 lasted for at least 3 h/d with HC diet feeding. Also, the LPS levels in the portal and hepatic veins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 48 publications
4
62
2
1
Order By: Relevance
“…In situations where these animals are not appropriately transitioned to concentrate-based diets, ruminal acidosis can occur [1]. Ruminal acidosis can negatively affect the integrity and barrier function of the rumen epithelium by increasing parakeratosis, vacuolation, and cell degeneration [2,3] The loss of barrier function in the rumen epithelium can lead to the translocation of bacteria, and its endotoxins (lipopolysaccharides), from the rumen into the systemic circulation and result in a hepatic acute phase response [4]. The acute phase response is caused by systemic inflammation and is characterized by the increase or decrease in acute phase reactants.…”
Section: Introductionmentioning
confidence: 99%
“…In situations where these animals are not appropriately transitioned to concentrate-based diets, ruminal acidosis can occur [1]. Ruminal acidosis can negatively affect the integrity and barrier function of the rumen epithelium by increasing parakeratosis, vacuolation, and cell degeneration [2,3] The loss of barrier function in the rumen epithelium can lead to the translocation of bacteria, and its endotoxins (lipopolysaccharides), from the rumen into the systemic circulation and result in a hepatic acute phase response [4]. The acute phase response is caused by systemic inflammation and is characterized by the increase or decrease in acute phase reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in agreement with the present study, Dong et al [29] reported that when the rumen pH of goats decreased to less than 5.8, plasma LPS value in the high-grain group was not significantly different from the low-grain groups. Elevated serum LPS levels as a result of SARA induction in cattle [9,14,33] are also expected in sheep. A possible reason for this discrepancy might be the insufficient sensitivity of LPS measurement methods in the studies on sheep and goats [12].…”
Section: Discussionmentioning
confidence: 96%
“…In other words, oral consumption of activated charcoal and zeolite in lambs with SARA resulted in significant reductions in serum LPS concentrations. There are enough understandings on pivotal role of LPS in causing multiple adverse sequels following SARA in ruminants [14,15,33]. It has been shown that as toxin binders, certain clay minerals such as bentonite and zeolite are able to trap free rumen bacterial toxins [23] and mycotoxins [34,35] in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations